Analysis of the maxillary sinuses and their extensions in digital panoramic radiographs (Research, Society and Development, 2023)
Panoramic radiography (PR) is one of the most used radiographic exams in dentistry, it analyzes bone structures such as the maxillary sinus (MS) and its extensions. The objective is to analyze in PRs, the main types of extensions in MS, such as alveolar and anterior extensions, tooth loss, relationship between tuberosity and the presence of third molars. In this cross-sectional study and quantitative, retrospective approach, by convenience sample, we verified the PRs of the Radiology Clinic of the Tiradentes University in the years 2019 and 2021, selecting patients over 18 years of age, examining 484 radiographs and 968 MWs. In the association between the variables, the non-parametric Chi-square test was used, with a statistical significance level of p